Transgenic Landscapes - Domingues, Álvaro (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2013)
An excessive polysemy has transformed landscape into a fluctuating concept, vague, precarious and colonisable by numerous meanings that act as metonymies—a figure of speech that consists in the use of one word as a substitute for another with which it is closely associated. In this way, a relation of mutual implication is established between the real object and the represented object, as the whole is represented by one of its parts and one thing is taken for another.